(untitled) (Acta Scientiarum. Biological Sciences, 2017)
The aim of this study was to investigate the diet composition and feeding strategies of Triportheus nematurus at the Miranda-Abobral floodplain region and evaluate if the temporal phenomenon of the flood pulse has influenced in the diet composition of the species. The fishes were sampled quarterly – between August/2014 and July/2016 – in the marginal ponds located in the Estrada Parque (MS 184). The feeding habits of T. nematurus was characterized as omnivorous and its opportunistic feeding behaviour, since its diet is composed of different resources along of the year. Insects and organic matter were the most important items during the drought period; plant material (leaves and roots) and Euglenophyceae algae were more expressive during the inundation period; insects and fruits were also abundant during the flood period. Through statistical analysis, it was possible to verify significant variation in the diet composition of the species. This variation in the components of the diet may be related to the availability of resources in the ponds throughout the year and reflect an already known pattern in Neotropical fish populations, which present high alimentary plasticity.